The Role of Time Preferences in Compliance With COVID-19 Preventive Behaviors in Iran: A Quasi-hyperbolic Discounting Approach - Moslem Soofi; Ali Kazemi Karyani; Shahin Soltani; Zahra Alipoor; Behzad Karamimatin (Journal of Preventive Medicine and Public Health)
Objectives: This study aimed to investigate the role of time preferences in compliance with coronavirus disease 2019 (COVID-19) preventive behaviors in an adult population of Iran. Methods: A web-based questionnaire was utilized to conduct a cross-sectional survey of 672 Iranian adults. The parameters of time preferences were estimated using a quasi-hyperbolic discounting model, and the relationship between COVID-19 preventive behaviors and time preferences was examined using a probit regression model. Results: A significant association was observed between the preventive behaviors of COVID-19 and the levels of patience and present-biased preferences among the study participants. Individuals who exhibited low levels of patience were found to be 12.8 percentage points less inclined to follow preventive behaviors compared to those with high levels of patience. The likelihood of having good preventive behaviors of COVID-19 was found to decrease by 14.3 percentage points among individuals with a present bias as opposed to those with a bias toward future. Conclusions: Patience and present-biased preferences are important determinants of adopting preventive behaviors against COVID-19. These behavioral characteristics should be considered in the design of control and prevention programs. Considering people’s discounting behavior and time (in)consistency in their preferences in the design of COVID-19 policy interventions can provide valuable insights for developing tailored public health policy interventions.